Management of renal cell carcinoma presenting during teenage pregnancy - Paige Koetter; Kathryn Martin, MD (Elsevier, 2020)
Renal cell carcinoma is uncommon in adolescence, especially when associated with pregnancy. We present the case of a 16 year old female who was found to have a large heterogeneous renal mass incidentally detected at 31 weeks gestation via pre-natal ultrasound. The patient delivered a healthy infant at 38 weeks gestation. She underwent left nephrectomy six weeks post-partum. This represents the youngest reported case of renal cell carcinoma during pregnancy. In this case report we review the differential diagnosis of renal masses in adolescents and discuss key management decisions involved in this case; specifically, the challenges of imaging and surgical planning during pregnancy. Management of abdominal masses during pregnancy must balance the health of the mother with that of the fetus.